Emerging integrase strand transfer inhibitor drug resistance mutations among children and adults on ART in Tanzania: findings from a national representative HIV drug resistance survey. (21st January 2023) - Kamori, Doreen; Barabona, Godfrey; Rugemalila, Joan; Maokola, Werner; Masoud, Salim S; Mizinduko, Mucho; Sabasaba, Amon; Ruhago, George; Sambu, Veryeh; Mushi, Jeremiah; Mgomella, George S; Mcollogi, James J; et al.
Abstract: Background: Despite the scale-up of ART and the rollout in Tanzania of dolutegravir, an integrase strand transfer inhibitor (INSTI), treatment success has not been fully realized. HIV drug resistance (HIVDR), including dolutegravir resistance, could be implicated in the notable suboptimal viral load (VL) suppression among HIV patients. Objectives: To determine the prevalence and patterns of acquired drug resistance mutations (DRMs) among children and adults in Tanzania. Methods: A national cross-sectional HIVDR survey was conducted among 866 children and 1173 adults. Genotyping was done on dried blood spot and/or plasma of participants with high HIV VL (≥1000 copies/mL). HIV genes (reverse transcriptase, protease and integrase) were amplified by PCR and directly sequenced. The Stanford HIVDR Database was used for HIVDR interpretation. Results: HIVDR genotyping was performed on blood samples from 137 participants (92 children and 45 adults) with VL ≥ 1000 copies/mL. The overall prevalence of HIV DRMs was 71.5%, with DRMs present in 78.3% of children and 57.8% of adults. Importantly, 5.8% of participants had INSTI DRMs including major DRMs: Q148K, E138K, G118R, G140A, T66A and R263K. NNRTI, NRTI and PI DRMs were also detected in 62.8%, 44.5% and 8% of participants, respectively. All the participants with major INSTI DRMs harboured DRMs targeting NRTI backbone drugs. Conclusions: More than 7 in 10 patients with high HIV viraemia in Tanzania have DRMs. The early emergence of dolutegravir resistance is of concern for the efficacy of the Tanzanian ART programme.